Simultaneous Inside and Outside Functionalization of Single-Walled Carbon Nanotubes - Kraus, Jan; Meingast, Laura; Hald, Janina; Beil, Sebastian B.; Biskupek, Johannes; Ritterhoff, Christian; Gsänger, Sebastian; Eisenkolb, Jasmin; Meyer, Bernd; Kaiser, Ute; Maultzsch, Janina; von Delius, Max (Angewandte Chemie International Edition, 2024)
Functionalizing single-walled carbon nanotubes (SWCNTs) in a robust way that does not affect the sp2 carbon framework is a considerable research challenge. Here we describe how triiodide salts of positively charged macrocycles can be used not only to functionalize SWCNTs from the outside, but simultaneously from the inside. We employed disulfide exchange in aqueous solvent to maximize the solvophobic effect and therefore achieve a high degree of macrocycle immobilization. Characterization by Raman spectroscopy, EDX-STEM and HR-TEM clearly showed that serendipitously this wet-chemical functionalization procedure also led to the encapsulation of polyiodide chains inside the nanotubes. The resulting three-shell composite materials are redox-active and experience an intriguing interplay of electrostatic, solvophobic and mechanical effects that could be of interest for applications in energy storage.
CRIS-Team Scopus Importer:2024-04-19
Keywords: disulfide exchange; HRTEM; polyiodide; Raman spectroscopy; SWCNT